ESIPT-based fluorescence probe for the rapid detection of peroxynitrite 'AND' biological thiols. Issue 80 (24th September 2018) - Wu, Luling; Han, Hai-Hao; Liu, Liyuan; Gardiner, Jordan E.; Sedgwick, Adam C.; Huang, Chusen; Bull, Steven D.; He, Xiao-Peng; James, Tony D.
Abstract : An ESIPT-based 'AND' logic fluorescence probe (GSH-ABAH ) was developed for the simultaneous detection of ONOO − 'AND' biological thiols. Abstract : An ESIPT-based 'AND' logic fluorescence probe (GSH-ABAH ) was developed for the simultaneous detection of ONOO − and biological thiols.GSH-ABAH was shown to have good cell permeability and with the addition of just SIN-1 (ONOO − donor) or GSH, no fluorescence response was observed in live cells. However, in the presence of both analytesGSH-ABAH could be used to image exogenous ONOO − 'AND' GSH added to RAW264.7 cells.